2019
DOI: 10.3389/fpsyg.2019.01446
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years Controlling Unwanted Thoughts: A Systematic Review of the Thought Control Ability Questionnaire (TCAQ)

Abstract: Thought control ability is a vulnerability factor implicated in the etiology and maintenance of emotional disorders. This manuscript aims to systematically review the use and psychometric performance of the Thought Control Ability Questionnaire (TCAQ), designed to assess people's ability to control unwanted thoughts. Three electronic databases were searched for papers administering the TCAQ published in indexed peer-reviewed journals. Data (participants characteristics, country, study design, etc.) were extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(126 reference statements)
2
16
0
Order By: Relevance
“…PTCA has been shown to be related to a reduction in frequency and intensity of negative, intrusive thoughts (Grisham & Williams, 2009; Williams et al, 2010), and since a central component of anxiety is having repetitive negative thoughts or worries that are difficult to control, it is not surprising that PTCA has the strongest relation with anxiety symptoms relative to any other variable. Taken together with previous research demonstrating inverse relationships between PTCA and trait anxiety (Feliu-Soler et al, 2019; Williams et al, 2010), the current study suggests that perceptions of the controllability of one’s thoughts appear to uniquely reduce risk for anxiety arousal and unwanted worry, however future longitudinal research further elucidating the relationship between PTCA and trait anxiety is certainly warranted. Other studies have also found links between PTCA and measures of specific anxiety disorders such as generalized anxiety disorder, as well as psychological disorders such as PTSD and schizophrenia, suggesting that PTCA may be useful as a transdiagnostic predictor of psychological disorders (Feliu-Soler et al, 2019, Gallagher et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…PTCA has been shown to be related to a reduction in frequency and intensity of negative, intrusive thoughts (Grisham & Williams, 2009; Williams et al, 2010), and since a central component of anxiety is having repetitive negative thoughts or worries that are difficult to control, it is not surprising that PTCA has the strongest relation with anxiety symptoms relative to any other variable. Taken together with previous research demonstrating inverse relationships between PTCA and trait anxiety (Feliu-Soler et al, 2019; Williams et al, 2010), the current study suggests that perceptions of the controllability of one’s thoughts appear to uniquely reduce risk for anxiety arousal and unwanted worry, however future longitudinal research further elucidating the relationship between PTCA and trait anxiety is certainly warranted. Other studies have also found links between PTCA and measures of specific anxiety disorders such as generalized anxiety disorder, as well as psychological disorders such as PTSD and schizophrenia, suggesting that PTCA may be useful as a transdiagnostic predictor of psychological disorders (Feliu-Soler et al, 2019, Gallagher et al, 2014).…”
Section: Discussionsupporting
confidence: 68%
“…Yet, research on PTCA has been very limited in terms of the populations studied. According to a recent review, the studies published in the past 15 years using the Thought Control Ability Questionnaire with samples from the U.S. consisted only of college students (Feliu-Soler et al, 2019).…”
Section: Obstacles To Psychological Well-beingmentioning
confidence: 99%
“…Thought Control Ability. For the current study, the 20-item version of the TCAQ (Williams et al, 2010) was utilised (see Feliu-Soler et al, 2019, for a review). The TCAQ assesses the perceived ability to control unwanted thoughts (e.g., "I often cannot avoid having upsetting thoughts").…”
Section: Psychotherapy Researchmentioning
confidence: 99%
“…To measure perceived thought control ability, the Thought Control Ability Questionnaire (TCAQ; Luciano et al 2005) will be used in the current research. A recent systematic review (Feliu-Soler et al 2019) revealed that this measure has been satisfactorily used in a variety of populationsincluding individuals from the general populations and patients with PTSD or clinical depressionand that the instrument has adequate dimensionality, reliability, and construct validity.…”
mentioning
confidence: 99%